TRAINING ON INTRODUCTION TO ECONOMIC TERMS IN INDONESIAN TO TGBC THAILAND STUDENTS - Sutianingsih Sutianingsih (LPPM ITB AAS Indonesia Surakarta, 2023)
The introduction of economic terms in Indonesia to other countries is very important because language is a very important communication tool to support a country's economic activities. Training activities were conducted on TGBC Thailand students. Knowing these economic terms, it is hoped that it can help trainees to understand simple economic terms in Indonesian., provide practical training in the use of these terms in daily communication and improve participants' ability to communicate related to the economy in the surrounding environment. As a result of this activity, the participants, namely TGBC Thailand students, were able to understand and pronounce simple economic terms were more interested in learning Indonesian and wanted to visit Indonesia. With so many tourists visiting Indonesia, economic activities will increase Keywords : Indonesian, Introduction of Economic Terms.